2023
DOI: 10.3389/fbioe.2023.1128268
|View full text |Cite
|
Sign up to set email alerts
|

Modification of PEG reduces the immunogenicity of biosynthetic gas vesicles

Abstract: Nanobubbles have received great attention in ultrasound molecular imaging due to their capability to pass through the vasculature and reach extravascular tissues. Recently, gas vesicles (GVs) from archaea have been reported as acoustic contrast agents, showing great potential for ultrasound molecular imaging. However, the immunogenicity and biosafety of GVs has not yet been investigated. In this study, we examined the immune responses and biosafety of biosynthetic GVs and polyethylene glycol (PEG)-modified GVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, it is noteworthy that GVs, composed of protein shells synthesized by bacteria, have a certain immunogenicity and can induce an immune response in mice. In our previous study, 46 PEG-GVs were successfully synthesized by PEG-coated GVs, and it was found that PEG-GVs greatly reduced the immunogenicity and reticuloendothelial system (RES) uptake, which provided a new idea for the clinical transformation of GVs in molecular imaging and disease diagnosis and treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that GVs, composed of protein shells synthesized by bacteria, have a certain immunogenicity and can induce an immune response in mice. In our previous study, 46 PEG-GVs were successfully synthesized by PEG-coated GVs, and it was found that PEG-GVs greatly reduced the immunogenicity and reticuloendothelial system (RES) uptake, which provided a new idea for the clinical transformation of GVs in molecular imaging and disease diagnosis and treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it improves the colloidal stability of nanoparticles, promoting their long-term dispersion in a liquid medium. Secondly, using PEG reduces the immunogenicity of nanoparticles, minimizing the potential immune response upon their introduction into a biological system [ 109 ]. Finally, PEG modification prolongs the circulation time of nanoparticles in vivo, enhancing their therapeutic effectiveness.…”
Section: Research On Polysaccharide-aunps As Drug Delivery Carriersmentioning
confidence: 99%
“…There is another research synthesizing ROS‐responsive prodrug by linking PTX with polyethylene glycol (PEG) chains via thioketal linkers and then co‐assembling with Ce6 to realize combined antitumor efficacy. [ 63 ]…”
Section: Ce6‐based Self‐assembled Nanoparticles For Combinational The...mentioning
confidence: 99%